Behavioral lateralization of mice varying in serotonin transporter genotype - Stieger, Binia; Wesseler, Yvonne; Kaiser, Sylvia; Sachser, Norbert; Richter, S. Helene (Frontiers in Behavioral Neuroscience, 2023)
In humans, non-right-handedness is associated with a higher incidence of psychiatric disorders. Since serotonin seems to be involved in both, the development of psychiatric disorders and lateralization, the present study focuses on the effect of the serotonin transporter (5-HTT) gene on behavioral lateralization. For this, we used the 5-HTT knockout mouse model, a well-established animal model for the study of human depression and anxiety disorders. For female mice from all three 5-HTT genotypes (wild type, heterozygous and homozygous knockout), we repeatedly observed the direction and strength of lateralization of the following four behaviors: grid climbing (GC), food-reaching in an artificial test situation (FRT), self-grooming (SG) and barrier crossing (BC), with the FRT being the standard test for assessing behavioral lateralization in mice. We found no association between behavioral lateralization and 5-HTT genotype. However, in accordance with previous findings, the strength and temporal consistency of lateralization differed between the four behaviors observed. In conclusion, since the 5-HTT genotype did not affect behavioral lateralization in mice, more research on other factors connected with behavioral lateralization and the development of symptoms of psychiatric disorders, such as environmental influences, is needed.